APLIKASI DIGITAL MARKETING UNTUK MENINGKATKAN OMZET PENJUALAN PRODUK KERAMIK HANDMADE NARUNA - Alvira, Regina Claudia (Inaque : Journal of Industrial and Quality Engineering, 2022)
The ceramic products discussed in this paper are hand-processed ceramic tableware with a competitive advantage in using the glazing technique at Naruna Ceramic Studio (NCS), Salatiga, Central Java, Indonesia. This technique is a coloring method after the first combustion of a ceramic kiln that can give a characteristic to the product giving an attractive and elegant color impression that can increase sales turnover and competitiveness of NCS compared to similar. The COVID-19 pandemic that continues to exist in Indonesia forces the number of customer sales to not be able to interact directly with NCS, so it is necessary to change a new marketing strategy carried out by NCS to increase turnover. The digital marketing method in this paper is applied by the author and NCS to market handmade ceramic tableware products with a finishing process using the glazing technique. The Digital Marketing System applied by NCS and researchers is to build an advertising platform that can influence consumer behavior so that it can make a significant contribution to increasing the turnover of this ceramic product seller. The ads that posted on Facebook, Instagram, YouTube, TikTok, and Website will be done will be based on the landing page which ends in the marketplace (Shopee, Tokopedia) and the WhatsApp application which is managed by NCS customer service. The final results up to October 2020 showed an increase in turnover of 65% after the implementation of this DM was implemented